2000
DOI: 10.1006/acha.2000.0276
|View full text |Cite
|
Sign up to set email alerts
|

Fast Algorithm for Best Anisotropic Walsh Bases and Relatives

Abstract: We introduce a new family of N log N best basis search algorithms for functions of more than one variable. These algorithms search the collection of anisotropic wavelet packet and cosine packet bases and output a minimum entropy basis for a given function. These algorithms are constructed after treating the model problem of computing best Walsh packet bases. Several intermediate algorithms for conducting mixed isotropic/anisotropic best basis searches in the function's various coordinate directions are also pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…In other words, we can impose that during our recursive binary splitting process, an n 1 × n 2 rectangle may only be split either into two n 1 /2 × n 2 rectangles, or into two n 1 × n 2 /2 rectangles. This scenario is similar to the anisotropic wavelet packets [1], [5]. 2 It can be shown that in this case, the total number of possible rectangular tiles is O (N 1 N 2 ), and therefore the computation of the costs has time and space complexity O (N 1 N 2 ).…”
Section: Optimal Rectangular Tilingsmentioning
confidence: 87%
See 4 more Smart Citations
“…In other words, we can impose that during our recursive binary splitting process, an n 1 × n 2 rectangle may only be split either into two n 1 /2 × n 2 rectangles, or into two n 1 × n 2 /2 rectangles. This scenario is similar to the anisotropic wavelet packets [1], [5]. 2 It can be shown that in this case, the total number of possible rectangular tiles is O (N 1 N 2 ), and therefore the computation of the costs has time and space complexity O (N 1 N 2 ).…”
Section: Optimal Rectangular Tilingsmentioning
confidence: 87%
“…A more flexible framework called anisotropic 2-D wavelet packets [1], [5], allows for any sequence of rowwise and columnwise applications of the decomposition operation (7), and is therefore a generalization of the classical wavelet packets.…”
Section: A Anisotropic Wavelet Packetsmentioning
confidence: 99%
See 3 more Smart Citations